Nomoi and Cannibalism in Herodotus' Histories - Baldwin, Ryan Masato (Histos, 2026)
This paper argues that Herodotus does not stigmatise cannibalism in his ethnographies. Rather than ‘Othering’ cannibalistic peoples like the Massagetae (1.216), Callatiae (3.38), Padaeans (3.99), and the Issedones (4.26), Herodotus’ depictions encourage his audience towards a stance of tolerance, while his depiction of the Androphagi (4.106) illustrates his reluctance to attach any particular custom as a marker of ‘Other’. In contrast, Herodotus denigrates cannibalism in his accounts of Cyaxares (1.73), Harpagus (1.119), and Cambyses’ Ethiopian campaign (3.25). I conclude with the suggestion that Herodotus’ depictions of distant peoples following their own custom even in this extreme case should be taken as further evidence of the historian’s cultural relativism.